Morphologic Analysis of the microstructural affectation of biocomposite material reinforced with fique fiber due to cutting with conventional tool, laser and water jet (2022)
Thanks to their properties, the use of composite materials in industrial applications has increased in recent decades, especially those with natural fiber reinforcements due to their lower environmental impact; however, one of the great challenges presented by this type of material is to shape them by cutting as their surface integrity can be compromised. In the present work, morphological analysis is carried out on a composite material with fique fiber, evaluating the superficial affectation by cutting made with a conventional tool, laser, and water jet. The material was made with six layers of fique fiber and polyester resin. The morphological study was carried out through scanning electron microscopy, where high defects were evidenced with the conventional tool, an affectation to the matrix in laser cutting, and a low surface impact using the water jet.